(untitled) (SCIÉNDO INGENIUM, 2025)
The continuous growing of the construction industry it is challenging to find the right choice for raw materials especially fibers for cement-based composites. In this study, raw Ichu fibers were evaluated to be used as reinforcement of cement matrices; mercerization treatment of the original fibers followed by the shear defibrillation technique were used to obtain the pulp; afterward, slurry-dewatering with the final pressing process technique were used to manufacture the composites boards. Results show that Ichu fibers required low aggressive mercerization treatment; furthermore, with mechanical shear defibrillation more than 80% of the defibrillated fiber present an aspect ratio over 80. The manufactured fiber cement composites board present a modulus of rupture over 8 MPa; moreover, with outdoor and indoor aging, samples modulus of rupture increases, reaching around 13.5 MPa for the outdoor aging; furthermore, progressive embrittlement was observed with impact over aging time. Finally, based on the mechanical properties of the boards, results suggest that with 9%wt of the Ichu pulp fibers as reinforcement, boards shown a bests characteristic.